Quest for justice - Tailer, Kathleen (Love inspired suspense., 2017)
"When her private investigator father is murdered, Bailey Cox stares down danger to find those responsible...and comes face-to-face with the cop who arrested her six years ago. But to uncover the secret that got her father killed, her former enemy must become her current ally. Franklin Kennedy's not convinced he can trust the ex-thief, but he needs her computer-hacking skills to crack this case. What the hard-nosed detective doesn't need is a soft spot for Bailey. But when their investigation leads them to international hired guns, Franklin realizes his mistake: he's put Bailey in their crosshairs..and time's running out to save her." -- Page [4] cover.